Dignidade da pessoa humana e autonomia da vontade : um estudo interdisciplinar sobre os limites éticos e jurídicos nos casos de eutanásia - Lima, Andrei Ferreira de Araújo (2018)
This work is the result of an interdisciplinary study between the Science of Law and Bioethics. It aims to understand the ethical and legal limits of the possible right to die, specifically euthanasia. In order to achieve that goal, we will investigate the conflict and the conformation between the fundamental right to life, to human dignity and the autonomy of the will, taking into account both doctrine and national and international jurisprudence. The main reason for the reincorporation of the subject of euthanasia into the medical and legal debate (both academic and jurisprudential) refers to the fast-moving and efficient evolution of medical science, developing treatments that can prolong the patient’s life, possibly, depending on the sickness, forever. In face of this reality, one can perceive the alteration of certain paradigms of Bioethics, such as the breaking of the paternalistic relationship between doctor and patient, the principle of beneficence according to what would be best for the patient, and the removal of unreasonable obstinacy, based on the autonomy of the will and in human dignity. In this scenario, the patients’ rights are increasingly debated and new contour to the state’s duty to protect life are being given, especially when in conflict with the dignity and autonomy of the patient. In this scenario, it’s debated a possible right to die with dignity. This right promotes numerous questions, especially concerning the ethical and legal limits in cases of euthanasia, requiring the establishment of clear criteria, having as a basic principle the maximum protection of the patient’s dignity. It is emphasized that, in spite of the varied forms of assisted death, as well as the recent incorporation of ortotanásia (term in Portuguese used for terminal patients who decline useless treatments and have their right to die granted) as legal conduct in medical ethics in Brazil, the work seeks to solve questions related to euthanasia. First classifying it, in order to avoid any form of semantic confusion. In the following points it will be discussed as a possible establishment of legal criteria as well as the practical developments, taking into account both the medical deontology and the patient’s fundamental rights.